Correlation and path analysis of durum wheat (Triticum turgidum L. Var. Durum) (Bangladesh Journal of Agricultural Research, 2013)
A study was conducted to examine relationship between important traits of durum wheat and their direct and indirect effects on grain yield. Research work was conducted during the winter season of 2009-10 under irrigated optimum seeding condition at Regional Agricultural Research Station, Bangladesh Agricultural Research Institute, Ishurdi, Pabna with 10 advanced genotypes. A wheat variety was used as check. Positive and significant correlation was found for plant height, spikes/m2, and 1000-grain weight with grain yield. Head days and maturity days showed considerable negative correlation with grain yield. Maturity days, spikes/m2, and 1000-grain weight had significant positive direct effects on grain yield. Grains/spike had direct positive effect but in low magnitude. The indirect effect of head days and plant height on grain yield was found mainly through maturity days and 1000-grain weight. It can be concluded that more emphasis should be given on head days and plant height along with 1000-grain weight, spikes/m2, and grains/spike during selection for dururn wheat improvement. DOI: http://dx.doi.org/10.3329/bjar.v38i3.16978 Bangladesh J. Agril. Res. 38(3): 515-521, September 2013